Association between dipeptidyl peptidase‐4 inhibitors and increased risk for bullous pemphigoid within 3 months from first use: A 5‐year population‐based cohort study using the Japanese National Database. Issue 3 (11th October 2021) - Kuwata, Hirohito; Nishioka, Yuichi; Noda, Tatsuya; Kubo, Shinichiro; Myojin, Tomoya; Higashino, Tsuneyuki; Takahashi, Yutaka; Ishii, Hitoshi; Imamura, Tomoaki
Abstract: Aims/Introduction: We assessed the association between dipeptidyl peptidase‐4 inhibitors (DPP‐4is) and bullous pemphigoid (BP) and time‐dependent changes in the risk for developing BP after DPP‐4i initiation. Materials and Methods: The present population‐based, real‐world study was carried out using the Japanese National Database dataset collected between 2013 and 2018. To assess independent correlations between DPP‐4is and the development of BP, the self‐controlled case series method was used. Results: Among the cohort followed up for a median of 1, 540 days, 53, 027 patients were likely to develop BP. The possible incidence rate of BP in all 150, 328, 339 patients was 10.4/100, 000 person‐years. Among the 9, 705, 814 patients with type 2 diabetes, 15, 634 were likely to develop BP. The possible incidence rate of BP in patients with type 2 diabetes was 38.1/100, 000 person‐years, whereas that in patients with type 2 diabetes who did and did not use DPP‐4is was 40.7 and 30.0/100, 000 person‐years, respectively. Analysis of the 28, 705 patients with type 2 diabetes likely to develop BP after initial DPP‐4i use showed a risk ratio of 2.15 (95% confidence interval [CI] 1.75–2.63), 1.70 (95% CI 1.37–2.11), 1.44 (95% CI 1.15–1.82), 1.25 (95% CI 0.98–1.59), 0.84 (95% CI 0.63–1.10), 0.84 (95% CI 0.64–1.11) and 1.05 (95% CI 0.92–1.20), for the risk period of ≤30, 31–60, 61–90, 91–120, 121–150, 151–180 and 181–365 days, respectively. Conclusions: Although DPP‐4is were associated with increased risk for BP, the risk was particularly significant within 3 months from first use. Abstract : We assessed the association between dipeptidyl peptidase‐4 inhibitors and bullous pemphigoid and time‐dependent changes in the risk for developing bullous pemphigoid after dipeptidyl peptidase‐4 inhibitor initiation. Although dipeptidyl peptidase‐4 inhibitors were associated with increased risk for bullous pemphigoid, the risk was significant within 3 months from first use.